Internet of Things (IoT) and its Utilisation in Marine Logistics - Abdul Haris Djalante (Collaborate, 2024)
The marine logistics industry is the backbone of global trade, responsible for the transport of more than 90% of goods traded worldwide. However, the industry faces challenges in terms of improving efficiency, reducing costs, and ensuring supply chain security and visibility. The Internet of Things (IoT), which refers to a network of physical devices, vehicles, and other objects equipped with sensors, software, and internet connectivity, is emerging as a potential solution to address these issues. This research aims to explore the role and utilization of IoT in improving the performance of the marine logistics industry. The methodology used includes a comprehensive literature review, in-depth interviews with industry experts, and case study analyses of IoT implementations in marine logistics companies. The results revealed several opportunities and benefits from IoT implementation, such as real-time container and cargo tracking, efficient vessel fleet management, route optimization and logistics planning, and improved supply chain security and safety. However, IoT implementation also faces challenges related to data security, interoperability, investment costs, and regulation. This research provides in-depth insights into how IoT can be leveraged to optimize marine logistics operations and improve industry competitiveness, as well as recommended solutions to overcome the challenges faced.